2004
DOI: 10.1002/eji.200425640
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation via Toll‐like receptor 9 reduces Cryptococcus neoformans‐induced pulmonary inflammation in an IL‐12‐dependent manner

Abstract: Cytosine‐phosphate‐guanosine‐containing oligodeoxynucleotides (CpG ODN) are important vaccine adjuvants that promote Th1‐type immune responses. Cryptococcus neoformans is a serious human pathogen that replicates in the lung but may disseminate systemically leading to meningitis, particularly in immunocompromised individuals. Immunization of susceptible C57BL/6 mice with CpG ODN deviates the immune response from a Th2‐ toward a Th1‐type response following infection with C. neoformans. CpG also induces IL‐12, TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
44
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 69 publications
3
44
0
Order By: Relevance
“…TLR9 recognizes as ligands viral and bacterial CpG-DNA motifs, which when bound to TLR9 on macrophages and DC, causes their activation [38][39][40]. A number of studies indicate that CpG-DNA TLR9 interaction can drive a Th1 immune response, as evidenced by a Th1-dominated cytokine profile [41][42][43]. A recent report demonstrated that TLR9 played an important role in the regulation of the mycobacteriainduced Th1 responses during M. tuberculosis infection in vivo [44].…”
Section: Introductionmentioning
confidence: 99%
“…TLR9 recognizes as ligands viral and bacterial CpG-DNA motifs, which when bound to TLR9 on macrophages and DC, causes their activation [38][39][40]. A number of studies indicate that CpG-DNA TLR9 interaction can drive a Th1 immune response, as evidenced by a Th1-dominated cytokine profile [41][42][43]. A recent report demonstrated that TLR9 played an important role in the regulation of the mycobacteriainduced Th1 responses during M. tuberculosis infection in vivo [44].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that TLR9 contributes to anticryptococcal host defenses. [52][53][54] Synthetic CpGDNA co-administered during C. neoformans infection enhances the development of Th1 response and reduces C. neoformans burden. 54 In addition, cooperative stimulation of DC by cryptococcal mannoproteins and CpG OligodN was demonstrated in vitro.…”
mentioning
confidence: 99%
“…[52][53][54] Synthetic CpGDNA co-administered during C. neoformans infection enhances the development of Th1 response and reduces C. neoformans burden. 54 In addition, cooperative stimulation of DC by cryptococcal mannoproteins and CpG OligodN was demonstrated in vitro. 53 Cryptococcal DNA and cell lysates have been shown to activate dendritic cell maturation and to induce IL-12 (pro-Th1 cytokine) production via TLR9 mediated mechanism in vitro.…”
mentioning
confidence: 99%
“…In addition to vaccination, protection of the mucosal surfaces can be elicited by several non-antigenic immune-stimulatory compounds; however, little is known about the molecular and cellular mechanisms associated with such generic protection (4,19,20). Pulmonary administration of CpG to the mouse lung protects from Cryptococcus neoformans challenge in an IL12-dependent manner (20).…”
mentioning
confidence: 99%
“…Pulmonary administration of CpG to the mouse lung protects from Cryptococcus neoformans challenge in an IL12-dependent manner (20). Similarly, up to 2 wk following the pulmonary administration of LTK63 mice are resistant to infections with respiratory syncytial virus (RSV), influenza virus, or C. neoformans.…”
mentioning
confidence: 99%